2014
DOI: 10.1371/journal.pgen.1004858
|View full text |Cite
|
Sign up to set email alerts
|

RA and FGF Signalling Are Required in the Zebrafish Otic Vesicle to Pattern and Maintain Ventral Otic Identities

Abstract: During development of the zebrafish inner ear, regional patterning in the ventral half of the otic vesicle establishes zones of gene expression that correspond to neurogenic, sensory and non-neural cell fates. FGF and Retinoic acid (RA) signalling from surrounding tissues are known to have an early role in otic placode induction and otic axial patterning, but how external signalling cues are translated into intrinsic patterning during otic vesicle (OV) stages is not yet understood. FGF and RA signalling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 67 publications
0
51
1
Order By: Relevance
“…Here we show the importance of place and time of neuroblast delamination in their allocation within the SAG, and shed light on how distinct information may converge in the progenitor cells. Delamination place confers position along the AP axis of the SAG, and therefore function, most probably as the result of the integration of patterning signals involved in the emergence of the different domains (Maier and Whitfield, 2014; Radosevic et al, 2011). Additionally, delamination time prefigures the relative position of early-delaminated neuroblasts vs. late-delaminated ones and therefore, the gradient of neuronal differentiation within the SAG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we show the importance of place and time of neuroblast delamination in their allocation within the SAG, and shed light on how distinct information may converge in the progenitor cells. Delamination place confers position along the AP axis of the SAG, and therefore function, most probably as the result of the integration of patterning signals involved in the emergence of the different domains (Maier and Whitfield, 2014; Radosevic et al, 2011). Additionally, delamination time prefigures the relative position of early-delaminated neuroblasts vs. late-delaminated ones and therefore, the gradient of neuronal differentiation within the SAG.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal vs. sensory specification is achieved through well-defined bHLH transcription factors: atoh1 for hair cell formation (Millimaki et al, 2007; Bermingham et al, 1999), neurog1 for sensory neuron determination (Andermann et al, 2002; Ma et al, 1998), and neuroD for sensory neuron differentiation and survival (Jahan et al, 2010; Kim et al, 2001). Signals arising in the surrounding tissues regionalize the otic vesicle along axes (Maier and Whitfield, 2014; Radosevic et al, 2011; Riccomagno et al, 2002, 2005; Sapède and Pujades, 2010), and this multiple step process implies a gradual restriction of cell fates over time (Whitfield and Hammond, 2007; Wu and Kelley, 2012). However, the phenotypes of targeted mutants for these signaling pathways are not always easy to reconcile (Raft and Groves, 2015), due to the limited comprehension of how developmental gene regulatory networks are integrated.…”
Section: Introductionmentioning
confidence: 99%
“…RA is also synthesized in the mouse otic vesicle, which expresses raldh3 (Mic et al, 2000). In zebrafish, RA and FGF signaling are essential for formation of the otic neurogenesis domain and production of otic neuroblasts (Maier & Whitfield, 2014). Loss of RA signaling through knockdown of RALDH enzymes or pharmacological inhibition resulted in hypoplastic otocysts in mice and zebrafish (Niederreither et al, 1999;Whitfield, Riley, Chiang, & Phillips, 2002).…”
Section: Otic Placodesmentioning
confidence: 99%
“…It is well accepted that RA generated from the underlying mesenchyme by RALDH activities participate directly in the specification of the neural tube along its anterior‐to‐posterior and dorsal‐to‐ventral axes . Similarly, RA from the periotic mesenchyme may control the regionalization of the developing otic epithelium in a stage‐dependent manner . In the chick, Raldh2 is expressed in the mesoderm caudal to the otic placode, and an appropriate spatial and temporal concentration of the diffusible RA is necessary for the correct specification of the anterior‐posterior axis of the developing otic anlagen .…”
Section: Discussionmentioning
confidence: 99%
“…20,39,42,51,54,[110][111][112][113] Similarly, RA from the periotic mesenchyme may control the regionalization of the developing otic epithelium in a stage-dependent manner. 9,10,15,29,107,[114][115][116][117] In the chick, Raldh2 is expressed in the mesoderm caudal to the otic placode, and an appropriate spatial and temporal concentration of the diffusible RA is necessary for the correct specification of the anteriorposterior axis of the developing otic anlagen. 114 In this sense, it has been suggested that the CYP1B1-mediated RA synthesis in the paraxial mesoderm could also participate directly in the dorsal-to-ventral specification of the developing neural tube in a paracrine manner.…”
Section: Cyp1b1 Expression At Otic Vesicle Stage: Patterning and Momentioning
confidence: 99%